Probing autoionizing decay in He atom with ultrashort laser pulses (2012)
ABSTRACT: A time dependent Feshbach method is implemented to study the correlated electron dynamics of He doubly excited states below the He+ (N=2) ionization threshold, using ultrashort laser pulses in XUV-pump IR-probe delay schemes.